FSKKP alumni system - Nur Aine, Omar (2009)
With the growing need for wireless Internet access, the web designers are now encountering a new challenge in creating support for mobility.Also,mobile access is based on different demand of information than conventional web usage.Wireless Application Protocol (WAP) enables easy fast delivery of relevant information and services to mobile users with wireless terminals with limited displays and data transfer capabilities.It is a specification for a set of communication protocols to standardize the way in which cellular devices use Internet access.The WAP technology which is implemented in an alumni system of Faculty Computer System and Software Engineering (FSKKP) is suitable for user who wants to be one of the alumni member club for a period time.The system contained 4 functions for members which are register function,search function,profile function,and news function.The problems that always occur are the difficulties to get the feedback from faculty ex-students about their life after graduate.From the research, there are several problems highlighted.It takes times to search for internet connection to register to be one of alumni members and also the students must connect to internet to view the alumni website to know the information about Faculty Computer System and Software Engineering (FSKKP),Nowadays, every alumni are built in website and members must online to know about the latest news of the alumni.Its causes the lack of attention from members because they prefer to focus on something else like mobile phone which more easily to bring and use.The objectives of this project are to develop alumni management system for FSKKP and to provide easier way for user to register as a part of alumni by using General Packet Radio Service (GPRS) in mobile service.